Dietary Microplastics: Exposure Pathways, Hotspots, and Organ-Specific Health Effects - Fitri, Agita Diora; M. Ramadhandie Odiesta; Tan Malaka; Indri Seta Septadina; Mariana (Side: Scientific Development Journal, 2026)
Microplastics (MPs) and nanoplastics (NPs) are pervasive environmental contaminants that increasingly infiltrate the human food chain, making dietary intake a continuous and unavoidable route of exposure. However, the integration of food-chain sources, exposure hotspots, biological absorption, and organ-specific health effects remains fragmented across the literature. This umbrella review synthesizes recent review-level evidence published between 2022 and 2025, focusing on farm-to-fork pathways of dietary microplastics, high-risk food contact materials—particularly tea bags and disposable cups—and mechanistic links to human health outcomes. Evidence indicates that microplastics originate from environmental contamination, food processing, packaging, and consumer-stage practices, with hot beverages representing a major but under-recognized exposure hotspot. Following ingestion, microplastics interact with the gastrointestinal tract, disrupt barrier integrity, and translocate systemically, accumulating in target organs including the liver, kidneys, endocrine organs, and reproductive tissues. Mechanistic pathways consistently involve oxidative stress, inflammatory signaling, endoplasmic reticulum stress, and endocrine disruption, often exacerbated by plastic-derived chemical additives. Despite growing concern, substantial methodological heterogeneity in detection and reporting limits quantitative risk assessment. Overall, dietary microplastics should be regarded as a multi-organ toxicological concern, underscoring the urgent need for standardized analytical frameworks and regulatory attention to food-contact materials and hot beverage consumption practices.